THE EFFECT OF WORKLOAD AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY AT THE OFFICE OF THE CENTRAL STATISTICS AGENCY OF TANAH DATAR REGENCY - Andri B, Alza Syofyan; Gusra, Wido Novaldi; Aima, M. Havidz; Yulasmi, Yulasmi (Gapenas Publisher, 2025)
The purpose of this study is to determine the influence of workload and work environment on employee work productivity. The sample technique used in this study is saturated sampling, so the sample obtained amounted to 47 people. Data analysis was carried out in several stages, namely 1) Validity Test was tested with Pearson correlation (r count > r table). 2) Reliability tested with Cronbach Alpha (> 0.60 is considered reliable). 3) Normality Test to find out whether the data is normally distributed or not 4) T test to find out the influence of each independent variable on the dependent variable. 5) F test to determine the influence of workload and work environment simultaneously on employee productivity at the headquarters of the Central Statistics Agency of Tanah Datar Regency. 6) Coefficient of Determination (R²) to find out how much contribution independent variables contribute in explaining dependent variables. Based on the results of the research and discussion that has been presented, the following conclusions can be drawn:. 1) Workload variables affect employee productivity at the Central Statistics Agency of Tanah Datar Regency. This means that the better the workload control, the higher the employee productivity level. 2) Work environment variables have a positive effect on employee productivity at the Central Statistics Agency of Tanah Data Regency. This means that the better the work environment for the institution, the more employee productivity will increase.3) Simultaneously, the workload, and the work environment have a positive effect on employee productivity at the Central Statistics Agency of Tanah Data Regency